Tumor-secreted IFI35 promotes proliferation and cytotoxic activity of CD8+ T cells through PI3K/AKT/mTOR signaling pathway in colorectal cancer - Li, Peisi; Zhou, Dawang; Chen, Dongwen; Cheng, Yikan; Chen, Yuan; Lin, Zhensen; Zhang, Xi; Huang, Zhihong; Cai, Jiawei; Huang, Wenfeng; Lin, Yanyun; Ke, Haoxian; et al. (Journal of biomedical science, 2023)
A large proportion of the patients with cancer do not respond to immunotherapies. Recent studies suggested an important role for tumor-infiltrating cytotoxic T lymphocytes (CTL) in enhancing response to immunotherapy. Here, we aim to identify gene that induce proliferative and cytotoxic states of CD8 T cells, and to investigate its effect on CAR-T cells against colorectal cancer. Correlation between the expression of IFI35 with the activation and cytotoxicity of CD8 T cells was assessed with TCGA and proteomic databases. Then we constructed murine colon cancer cells over-expressing IFI35 and tested their effect on anti-tumor immunity in both immunodeficient and immunocompetent mouse models. Flow cytometry and immunohistochemistry were performed to assess the immune microenvironment. Western blot analysis was used to identify the potential down-stream signaling pathway regulated by IFI35. We further investigated the efficacy of the rhIFI35 protein in combination with immunotherapeutic treatment. The transcriptional and proteomic analysis of the activation and cytotoxicity of CD8 T cells in human cancer samples demonstrated that IFI35 expression is correlated with increased CD8 T cell infiltration and predicted a better outcome in colorectal cancer. The number and cytotoxicity of CD8 T cells were significantly increased in IFI35-overexpressing tumors. Mechanistically, we identified that the IFNγ-STAT1-IRF7 axis stimulated IFI35 expression, and that IFI35-mediated regulation of CD8 T cell proliferation and cytotoxicity was dependent on PI3K/AKT/mTOR signaling pathway in vitro. Furthermore, IFI35 protein enhanced the efficacy of CAR-T cells against colorectal cancer cells. Our findings identify IFI35 as a new biomarker that can enhance the proliferation and function of CD8 T cells, as well as increase the efficacy of CAR-T cells against colorectal cancer cells.